The effects of CT-based attenuation correction on the accuracy of 99mtc SPECT/CT quantification - Vijayakumar, Shamalah S (Universiti Sains Malaysia, 2024)
This study focuses on how CT- based attenuation correction affects the precision of quantification using Technetium-99m (99mTc) single-photon emission computed tomography/computed tomography (SPECT/CT). Functional and anatomical imaging are combined in SPECT/CT in nuclear medicine which is essential for precise diagnosis and therapy planning. To reduce patient exposure while retaining the image quality, CT scan radiation doses must be lowered. Therefore, this study investigates how varying CT current (mA) affects 99mTc SPECT/CT image quality overall and photon attenuation correction accuracy. In terms of methodology, the study used NEMA 2012/IEC 2008 phantoms filled with 99mTc and the GE Discovery NM/CT 670 Pro SPECT/CT system, using tumor-to-background ratios (TBR) of 4:1 and 10:1. The effects of various mA levels (30, 60, 90, 100, and 120 mA) on quantification accuracy and image quality were investigated. Image quantification and reconstruction were made easier using the Q.Metrix software and the Xeleris workstation, respectively. To evaluate the quality of the images, important metrics like contrast, signal-to-noise ratio (SNR) and coefficient of variation (COV) were examined. Recovery coefficients (RC) were utilised for quantitative analysis. According to the findings, low-dose CT which is accomplished by reducing the tube current can generate images with sufficient quality for precise quantification in 99mTc SPECT/CT. The study supports the ALARA (As Low As Reasonably Achievable) principle by showing that radiation exposure to patients can be decreased without sacrificing diagnostic accuracy. The significance of these findings lies in their potential to improve patient safety by lowering radiation doses while maintaining accurate and trustworthy diagnostic imaging.